PEREMPUAN DI HADAPAN TUHAN (Pemikiran Feminisme Fatima Mernissi) - Muhammad Rusydi (An Nisa'a, 2012)
In discourses of Moslem feminist, the difference of physical and biologist that given is not questioned again, because questioning that matter is comprehended as effort intervention to God power. However questioned is why the difference having the character of that given caused the differentiation of woman ability in region (read: public-private / domestication) or their role (public-private) in social level, cultural, and also the religion. Elementary matter like that's causing, one feminism movement appearance side and on the other hand academically emerge also analyses gender. This article farther wish to know how feminism Fatima Mernissi opinion in the middle of though constellation about feminism that in the last decade in such a way massif.